PENERAPAN MATERIAL FLOW COST ACCOUNTING (MFCA) UNTUK MENGUNGKAP BIAYA TERSEMBUNYI LIMBAH PADA UMKM KAFE : STUDI KASUS PADA KAFE DAN PASTRY DI KOTA MAKASSAR - Hairul Mar’i; Salsabila Arianto; Linda Arisanty Razak; Ismail Badollahi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This study aims to reveal the hidden costs of material loss that have long been invisible in the conventional financial records of a café and pastry micro-enterprise (SME) in Makassar. The problem addressed is that small-scale cost accounting typically stops at cash-based profit and loss and records all material purchases as a single Cost of Goods Sold, leaving wasted materials unmeasured and unmanaged. Using a qualitative single-case-study approach, the research applies Material Flow Cost Accounting (MFCA) based on ISO 14051:2011 to trace material flows across four quantity centers and to allocate four cost elements—material, energy, system, and waste management—between product and non-product output. Because full physical weighing was not feasible, an estimative MFCA approach combined owner estimates with actual purchase prices from the financial records. The results show that total non-product output reached approximately IDR 2,350,850 per month, equivalent to 9.4% of total monthly operating cost, with an annual projection exceeding IDR 28 million that had never been recorded as a loss. The study concludes that sustainability accounting is affordable and feasible for SMEs using already-available data, and that MFCA information meaningfully supports efficiency decisions by the owner.